Zooplankton map - Abu Seman, Nur Alya Farzana; Idris, Nurul Syafinaz; Kamaruddin, Sharir Aizat; Hashim, Aimie Rifhan; Mat Nazir, Eliy Nazira (Universiti Teknologi Mara, Kedah, 2022)
Zooplankton is necessary for many aquatic creatures, such as fish, seahorses, clams, and bacteria, as they play an important role in the aquatic food web. Due to their importance, their distribution in our aquatic environment should be mapped as baseline information. The objective of our innovation is to produce maps of zooplankton. The name of our product is Zooplankton Map. To date, there has been no development of a zooplankton map, especially in the northern region of Malaysia, which gave extra advantages to our product. In terms of community benefits, Zooplankton Map will help many clients such as local, government and non-government bodies. Overall, Zooplankton Map is consistent with the Sustainable Development Goals established by the United Nations SDG 14: "Life below water," SDG 2: "Zero hunger," SDG 3: "Good health and well-being," and SDG 13: "Climate action”.